FT-Raman and chemometric tools for rapid determination of quality parameters in milk powder: Classification of samples for the presence of lactose and fraud detection by addition of maltodextrin. (1st April 2016) - Rodrigues Júnior, Paulo Henrique; de Sá Oliveira, Kamila; Almeida, Carlos Eduardo Rocha de; De Oliveira, Luiz Fernando Cappa; Stephani, Rodrigo; Pinto, Michele da Silva; Carvalho, Antônio Fernandes de; Perrone, Ítalo Tuler
Highlights: Whole-lactose and low-lactose milk powder was produced. Some milk powder samples was adulterated with maltodextrin. Raman spectra were obtained from all samples. The samples were characterized based on their characteristics Raman bands. Chemometric tools allowed to classify all samples correctly. Abstract: FT-Raman spectroscopy has been explored as a quick screening method to evaluate the presence of lactose and identify milk powder samples adulterated with maltodextrin (2.5–50% w/w). Raman measurements can easily differentiate samples of milk powder, without the need for sample preparation, while traditional quality control methods, including high performance liquid chromatography, are cumbersome and slow. FT-Raman spectra were obtained from samples of whole lactose and low-lactose milk powder, both without and with addition of maltodextrin. Differences were observed between the spectra involved in identifying samples with low lactose content, as well as adulterated samples. Exploratory data analysis using Raman spectroscopy and multivariate analysis was also developed to classify samples with PCA and PLS-DA. The PLS-DA models obtained allowed to correctly classify all samples. These results demonstrate the utility of FT-Raman spectroscopy in combination with chemometrics to infer about the quality of milk powder.